The Role of Animal Assisted Intervention on Improving Self-Esteem in Children With Attention Deficit/Hyperactivity Disorder - Schuck, Sabrina E. B.; Johnson, Heather L.; Abdullah, Maryam M.; Stehli, Annamarie; Fine, Aubrey H.; Lakes, Kimberley D. (Frontiers in Pediatrics, 2018)
Attention Deficit/Hyperactivity Disorder (ADHD), the most ubiquitous mental health problem in children, has been associated with poor self-esteem. Psychosocial interventions have aimed to improve self-esteem among this group, with the aim of reducing the development of comorbid depression and anxiety. The present study implemented a randomized control design to examine the possibility of Animal Assisted Interventions (AAI) as a viable approach to improving self-esteem among children with ADHD. Children's self-esteem across multiple domains as measured by the Self-Perception Profile for Children was evaluated (n = 80, ages 7–9, 71% male). To test the hypothesis that AAI improves self-esteem, stratified Wilcoxon Signed-Rank Tests (SAS NPAR1WAY procedure) were used to compare pre- to post-treatment ratings. Analyses indicated that scores of children's self-perceptions in the domains of behavioral conduct, social, and scholastic competence, were significantly increased from baseline to post-treatment in the AAI group (z = 2.320, p = .021, z = 2.631, p = .008, and z = 2.541, p = .011, respectively), whereas pre-post-treatment differences in self-perceptions were not found for the children in the control group without AAI. Findings suggest that AAI is a viable strategy for improving ratings of self-perceived self-esteem in children with ADHD.